The role of ecolabels in the Finnish wine sector from wine importers' perspective - Keinänen, Jenni (My University, 2021)
Environmental issues have become a growing concern of business. To address the challenges of sustainable business, many organizations have developed different ecolabels, and the number of these labels has increased notably during the last few decades. Wine sector members, too, have become increasingly interested in adopting more sustainable practices, and ecolabels have become a common way of communicating about the environmental aspects of wine. While there exists quite a lot of literature concerning ecolabels and wine business from consumer and producer perspective, wine importers are a group that has been overlooked by prior research. In Finland, there is a state monopoly for alcoholic beverages containing more than 5.5 percent of alcohol by volume, so as a marketplace for wine it differs from that of many other countries. The Finnish alcohol monopoly Alko sells products that have been bought from domestic and foreign alcohol businesses, which places wine importers in a major role in the Finnish wine market. This thesis studies the perceptions of Finnish wine importers regarding environmental label’s role in the Finnish wine sector. The purpose of this research is divided into four sub-questions: how ecolabels have influenced the Finnish wine market, what are the advantages and strengths of ecolabels, what are the disadvantages and weaknesses of ecolabels, and what influence ecolabels will have on the Finnish wine market in the future. The theoretical background of the thesis is tied to corporate environmental responsibility (CER), ecolabels, and environmental concerns of the wine business. The research method used for this thesis was theme interview. The themes discussed during the interviews were based on the four sub-questions of this research. Six interviews were conducted with representatives of Finnish wine importers. There was also a preliminary interview with Alko’s sustainability manager to gain a better understanding on the topic before the interviews with importers’ representatives. The interviews were conducted between 17.2.2020 and 26.10.2020. The results of this study indicate that ecolabels have a substantial role in the Finnish wine sector. The interviewees perceived that the consumer demand for ecolabelled wine has increased, and that Alko’s actions have contributed to the growing role of environmental labels in the Finnish wine market. Ecolabels were perceived to have several advantages, most significant of which including responding to consumer demand and promoting environmental responsibility. Interviewees’ views on the disadvantages of environmental labels were quite varied. They included such as rigidity of environmental labels, expensiveness of ecolabelling, and the large number of labels when it leads to confusion among consumers. Ecolabels were expected to have a growing significance for the Finnish wine sector in the future, while there still seems to be a call for raising consumer awareness of the contents of labels and how ecolabelling can affect the price of wine.

Ympäristöongelmista on tullut kasvava huolenaihe liike-elämässä. Kestävän liiketoiminnan haasteiden ratkaisemiseksi monet organisaatiot ovat kehittäneet erilaisia ympäristömerkkejä ja näiden merkintöjen määrä onkin kasvanut huomattavasti viime vuosikymmenien aikana. Myös viinialan eri toimijat ovat yhä kiinnostuneempia kestävän kehityksen mukaisten käytäntöjen omaksumisesta. Ympäristömerkeistä on tullut yleinen tapa kommunikoida viinin ominaisuuksista ympäristönäkökulmasta. Ympäristömerkkejä ja viinialaa on tutkittu melko laajasti kuluttajien ja tuottajien näkökulmasta, mutta viinin maahantuojat ovat ryhmä, joka on jätetty huomiotta aikaisemmissa tutkimuksissa. Suomessa on valtion monopoli koskien juomia, jotka sisältävät alkoholia yli 5,5 tilavuusprosenttia, joten viinin markkinapaikkana Suomi eroaa monista muista maista. Suomalainen alkoholimonopoli Alko hankkii myymänsä tuotteet koti- ja ulkomaisilta alkoholialan yrityksiltä, mikä asettaa viinin maahantuojat merkittävään rooliin Suomen viinimarkkinoilla. Tämän tutkielman tarkoitus on tutkia suomalaisten viinin maahantuojien käsityksiä koskien ympäristömerkkien roolia Suomen viinialalla. Tutkimuksen päätutkimuskysymys on jaettu neljään alakysymykseen: miten ympäristömerkit ovat vaikuttaneet Suomen viinimarkkinoihin, mitä ovat ympäristömerkkien edut ja vahvuudet, mitä ovat ympäristömerkkien haitat ja heikkoudet sekä millä tavalla ympäristömerkit vaikuttavat Suomen viinimarkkinoihin tulevaisuudessa. Tämän tutkielman teoreettinen tausta nivoutuu yritysten ympäristövastuuseen, ympäristömerkkeihin ja viinialan ympäristöongelmiin. Tässä opinnäytetyössä käytettiin tutkimusmenetelmänä teemahaastattelua. Haastattelujen aikana käsitellyt teemat perustuivat tämän tutkimuksen neljään alakysymykseen. Tutkielmaa varten haastateltiin kuutta suomalaisten viinin maahantuojien edustajaa. Ennen maahantuojien edustajien haastatteluja käytiin myös alustava haastattelu Alkon kestävän kehityksen johtajan kanssa, jotta aiheesta saataisiin kokonaisuudessaan parempi käsitys. Haastattelut tehtiin aikavälillä 17.2.2020 - 26.10.2020. Tämän tutkimuksen tulokset osoittavat, että ympäristömerkeillä on merkittävä rooli Suomen viinimarkkinoilla. Haastateltavat kokivat, että kuluttajakysyntä ympäristömerkityille viineille on noussut ja että Alkon toiminta on edistänyt ympäristömerkkien kasvavaa merkitystä Suomen viinimarkkinoilla. Ympäristömerkeillä koettiin olevan useita etuja, joista merkittävimpiä olivat kuluttajakysyntään vastaaminen ja ympäristövastuun edistäminen. Haastateltavien näkemykset ympäristömerkkien haitoista olivat vaihtelevia ja niihin kuuluivat muun muassa ympäristömerkkien joustamattomuus, ympäristömerkkien kallis hinta ja suuri määrä erilaisia ympäristömerkintöjä, silloin kun se johtaa sekaannukseen kuluttajien keskuudessa. Ympäristömerkeillä odotettiin olevan kasvava merkitys Suomen viinialalle tulevaisuudessa, vaikkakin yhä on olemassa tarve kuluttajien tietoisuuden lisäämiseen koskien ympäristömerkkien sisältöä ja sitä, miten ne vaikuttavat viinin hintaan.
Keywords: ecolabels, environmental labels, sustainability, wine, corporate environmental responsibility, importer